(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The article, based on linguoterminological data, examines the scientific achievements of modern astronomy and cosmology, lexical units related to these areas - terms, words and phrases, as well as theoretical issues related to the place and use of lexical units in the education system and discourse analysis.